Factors prompting and deterring suicides on the roads. Issue 3 (3rd May 2023) - Norman, Hilary; Marzano, Lisa; Winter, Rachel; Crivatu, Ioana; Mackenzie, Jay-Marie; Marsh, Ian
Abstract : Background: In addition to the devastating impact on the individual and their families, suicides on the roads can cause distress and harm to other people who might be involved in a collision or witness an attempt. Despite an increased focus on the characteristics and circumstances of road-related suicides, little is known about why people choose to end their lives in this way. Aims: The aim of the current study was to investigate the factors prompting and deterring the decision to attempt suicide on the roads. Method: We conducted a secondary analysis of survey data, as well as seven in-depth qualitative interviews. Participants had lived experience of suicidal ideation or behaviour at a bridge or road location. We also carried out an online ethnography to explore interactions in different online communities relating to this method of suicide. Results: Participants perceived a road-related suicide to be quick, lethal, easy and accessible and to have the potential to appear accidental. The proportion of participants who described their thoughts and attempts as impulsive appeared to be higher than had been observed with other method choices. The potential impact on other people was a strongly dissuasive factor. Conclusions: Measures designed to prevent access to potentially lethal sites may be particularly important, given that many participants described their thoughts and behaviour as impulsive. In addition, fostering a culture of care and consideration for other road users may help to dissuade people from taking action on the roads.